Testicular Sperm for Intracytoplasmic Sperm Injection in Oligozoospermic Men with High Sperm DNA Fragmentation, To Do or Not To Do - Allameh, Farzad; Abedi, Amirreza; Karimi, Maryam; Fallah-Karkan, Morteza (Archives of Men's Health, 2019)
-